2011
DOI: 10.1016/j.exer.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 20-HETE attenuates diabetes-induced decreases in retinal hemodynamics

Abstract: The mechanisms of early diabetes-induced decreases in retinal blood flow have yet to be fully determined. The aim of this study was to explore the hypothesis that 20-hydroxyeicosatetraenoic acid (20-HETE) plays a role in the early decrease of retinal hemodynamics in diabetic mice. 20-HETE has been implicated previously in the diabetes-enhanced vasoconstriction of mesenteric and renal vessels; however, its role in the diabetic retinal microcirculation has not been investigated. Diabetes was induced by multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 25 publications
3
31
2
Order By: Relevance
“…They are also similar to other reported reductions in F values in STZ-diabetic mice. 3236 Had these investigators measured O 2A , it is likely that they would have found decreases in DO 2 similar to the decrease of 43% in the current study. These defective DO 2 and F responses in diabetes likely correspond to the well-known impaired autoregulation seen in humans with diabetes.…”
Section: Discussionsupporting
confidence: 61%
“…They are also similar to other reported reductions in F values in STZ-diabetic mice. 3236 Had these investigators measured O 2A , it is likely that they would have found decreases in DO 2 similar to the decrease of 43% in the current study. These defective DO 2 and F responses in diabetes likely correspond to the well-known impaired autoregulation seen in humans with diabetes.…”
Section: Discussionsupporting
confidence: 61%
“…Similar to early human DR, we observe significant decreases in retinal blood flow rates in the initial weeks of hyperglycemia in diabetic rats and mice (Lee and Harris 2008; Lee et al, 2008; Wright and Harris 2008; Wright et al, 2009; Wang et al, 2010; Wang et al, 2011; Yadav and Harris 2011). The magnitude of the decrease within the first several weeks of developing hyperglycemia in rodents is ~25-40%, very similar to the change seen in early human DR.…”
Section: Introductionsupporting
confidence: 62%
“…fRBC imaging has been used to measure capillary flux and velocity by tracking the movement of labeled cells in video frames (Ben-Nun et al, 1992; Yamaguchi et al, 1992; Hudetz et al, 1995; Ben-Nun, 1996; Parthasarathi et al, 1999; Seylaz et al, 1999; Krolo and Hudetz, 2000; Schulte et al, 2003; Reyes-Aldasoro et al, 2008; Wright and Harris, 2008; Wang et al, 2011). With advances in imaging technology, fRBCs have also been tracked with confocal microscopy (Villringer et al, 1994; Pinard et al, 2002; Tomita et al, 2011) and scanning laser ophthalmoscopy (Wajer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%